Building an early warning towards the resilience of Islamic Banking in Indonesia - Kusuma, Dimas Bagus; Duasa, Jarita (Faculty Of Shariah and Law Syarif Syarif Hidayatullah State University Jakarta, 2017)
An early warning system (EWS) is widely used as surveillance mechanism for preserving financial system stability. This paper addresses the issue of namely which macroeconomic indicators that are capable of signaling adverse shocks towards the resilience of Islamic banking in Indonesia. This research uses an extraction signal approach as EWS mechanism. The results suggest that there are several indicators that (1) IBRI, which is composed from standardized deposit and financing, is able to figure out the resilience of Islamic banking. The resilience of Islamic banking was considered stable since the index was moving below the normal line during the global financial crises, and (2) Some selected macro financial indicators, M2/reserve (M2res), credit growth (CG), real effective exchange rate (REER), and inflation rate (INF) empirically show low noise to signal ratio. It means that these four variables are capable of signaling vulnerabilities due to adverse external shocks. The paper recommends that the resilience of Islamic banking needs to be supported by the resilience in the real sector.